2018
DOI: 10.1007/s10493-018-0249-8
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal and repellent effects of Cnidium officinale-derived material against Dermanyssus gallinae (Acari: Dermanyssidae)

Abstract: The acaricidal activity of a methanolic extract and fractions from the rhizome of Cnidium officinale against Dermanyssus gallinae adults was investigated. The C. officinale methanolic extract exhibited 100% acaricidal activity after 48 h of treatment at a dose of 4000 ppm. The acaricidal constituents of the plant were sequentially partitioned with several solvents and then purified using silica gel column chromatography and high-performance liquid chromatography. Gas chromatography-mass spectrometry and nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The resin of Commiphora holtziana spp. holtziana (gum haggar), extracts of Conocarpus erectus, methanolic extracts and fractions of Cnidium officinale (Kim et al 2018), and several essential oils, including thyme (Thymus vulgaris), have shown significant repellency during in vitro tests (Table 1). It is worth noting that some of these plantderived sub stances are also known for their toxic properties to D. gallinae (C. officinale, Kim et al 2004; manuka (Leptospermum scoparium), thyme (T. vulgaris), clove bud (Syzygium aromaticum = Eugenia caryophyllata), George et al 2010).…”
Section: Plant Parts and Plant Extractsmentioning
confidence: 99%
“…The resin of Commiphora holtziana spp. holtziana (gum haggar), extracts of Conocarpus erectus, methanolic extracts and fractions of Cnidium officinale (Kim et al 2018), and several essential oils, including thyme (Thymus vulgaris), have shown significant repellency during in vitro tests (Table 1). It is worth noting that some of these plantderived sub stances are also known for their toxic properties to D. gallinae (C. officinale, Kim et al 2004; manuka (Leptospermum scoparium), thyme (T. vulgaris), clove bud (Syzygium aromaticum = Eugenia caryophyllata), George et al 2010).…”
Section: Plant Parts and Plant Extractsmentioning
confidence: 99%
“…Nevertheless, the repellent effect described here was unclear, as it was not possible to distinguish the contact and olfactive repellent effects. In another study, the acaricidal and repellent activities of a methanolic extract and fractions from the rhizome of Cnidium officinale were tested to control D. gallinae (Kim et al ., 2018). Kim et al .…”
Section: Repulsive Substancesmentioning
confidence: 99%
“…Kim et al . (2018) showed that the methanolic extract of C. officinale has a 91.3% repellent activity on PRM, while (Z)-ligustilide, which is an isolated compound from C. officinale roots, showed a repellent response rate equal to 100% using a T-tube olfactometer.…”
Section: Repulsive Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chicken farms in South Korea and Europe have suffered severely from exposure to residual pesticides used to protect hens from red mite [1,2]. Billions of chicken eggs exposed to the toxic chemicals were discarded for safety reasons because they were unusable as food.…”
Section: Introductionmentioning
confidence: 99%